Narrative review: strengthening students’ self-identity through Christian values-based guidance and counseling services - Anggita, Inggar; Ramli, M.; Muslihati, Muslihati (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
Adolescence is an important stage for self-identity discovery. Thus, effective guidance and counseling strategies are needed in shaping students’ self-identity. One of them is by integrating Christian values in guidance and counseling services. This article is aimed to analyze the shaping of self-identity through guidance and counseling services based on Christian values. Narrative review is used to compile several published articles and research studies from Google scholars with the key words “guidance and counseling services based on Christian values” and “integration of Christian values in counseling and psychology”. Hence, 80 journals from 54 national and 26 international journals are collected, with 7 national journals selected with the PRISMA model. The result of this article covers 4 key areas in guidance and counseling services with Christian values :1)Guidance and counseling services can be applied through prayer and Scripture reading that are suitable for students’ needs, 2)Guidance services are conducted to help students to be independent and discipline, 3)Counseling services can be done through pastoral counseling and discipleship,4)School counselor has an important role to instill Christian values in shaping students’ self-identity.